A quantum science space station. (1st January 2023) - Thompson, Rob; Mahageg, Makan; Kellogg, Jim; Mosher, Todd; Ramadorai, Ray; Ruttley, Tara; Wagner, Erika; Woerner, Lisa
Abstract: In the coming years we expect to see a diverse array of quantum instruments being developed and flown in space, including quantum gas experiments, optical clocks, atom interferometry experiments, and quantum information/quantum optics experiments. The International Space Station has proven itself as an exceptional platform for such missions, providing long-term microgravity in a pressurized and temperature controlled environment, with ample power, thermal and data resources. However the station is currently planned to operate only through 2030, well before many proposed quantum sciences missions could be ready for launch, and we undertake here to explore what an ideal follow-on platform might look like. In particular, we believe that a much smaller and less expensive low Earth orbiting facility, optimized and dedicated to quantum science, could be an exceptionally powerful platform for exploring the quantum world and harnessing quantum technology. Such a platform would allow multiple quantum instruments to share resources and explore related phenomena in concert.